2008
DOI: 10.1016/j.jinteco.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

New evidence on the puzzles: Results from agnostic identification on monetary policy and exchange rates

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
151
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(173 citation statements)
references
References 40 publications
17
151
5
Order By: Relevance
“…Why do our results differ from Faust and Roger (2003) and Scholl and Uhlig (2005) with regard to the response in the exchange rate? 17 Neither of these papers restrict the interaction between monetary policy and the exchange rate, but rely instead on a series of sign restrictions for identification.…”
Section: Robustness Of Resultscontrasting
confidence: 80%
See 2 more Smart Citations
“…Why do our results differ from Faust and Roger (2003) and Scholl and Uhlig (2005) with regard to the response in the exchange rate? 17 Neither of these papers restrict the interaction between monetary policy and the exchange rate, but rely instead on a series of sign restrictions for identification.…”
Section: Robustness Of Resultscontrasting
confidence: 80%
“…However, the effect is not uniquely identified, so no robust conclusions can be drawn with regard to the exact timing of the peak response, which could be immediate or delayed. Similar results are also found in Scholl and Uhlig (2005), using a procedure related to that of Faust and Rogers (2003).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…1 The relation between interest rate differentials and subsequent exchange rate movements has been extensively investigated. Eichenbaum and Evans (1995), Faust and Rogers (2003), and Scholl and Uhlig (2008) conduct empirical research on the forward premium and delayed overshooting puzzles while Gourinchas and Tornell (2004) and Bacchetta and van Wincoop (2010) show that an increase in the interest rate can cause sustained exchange rate appreciation if investors either systematically underestimate the persistence of interest rate shocks or make infrequent portfolio decisions. Based on this research, we postulate the following exchange rate forecasting equation 2 : g g * ⊗et+1 = ω − ωuππt + ω fππ t * − ωuy yt + ω fy yt…”
Section: Taylor Rule Fundamentals Modelmentioning
confidence: 99%
“…Eichenbaum & Evans (1995) examined the period between 1974 and 1990 and found that expansionary U.S. monetary shock had initially led to an appreciation of the U.S. dollar, but which subsequently depreciated over two to three years. Scholl & Uhlig (2008) showed the existence of delayed overshooting for USA vis-à-vis the exchange rates of Germany, UK, Japan and G7 countries for the period between 1975 and 2002. Kim (2005) argued that the intervention of the central bank on foreign exchange markets is the main reason for delayed overshooting for the Canadian-US bilateral exchange rates.…”
Section: Literature Reviewmentioning
confidence: 99%